The Determinants of Credit Risk: Evidences from Chinese Commercial Banks - Wang, Yihui (2020)
Credit risk has become a major risk for the banking and financial sector following the 2008 global financial crisis. Yet, there is very little literature on the determinants of credit risk in Chinese commercial banks. This paper analysis bank-level determinants of credit risk for all 229 commercial banks in China over the period 2010–2019. Due to data availability, the data set is an unbalanced panel with 656 observations. There are seven bank-specific variables employed in this paper, including bank profitability, liquidity ratio, bank size, cost efficiency, loan loss reserve ratio, income diversification and bank capitalization, while three macro-control variables are GDP growth rate, inflation rate and lending interest rate, respectively. Using both fixed effect and two-step system GMM estimation, the empirical findings of this paper suggest that greater bank profitability, larger bank size and more income diversification reduce the probability of defaults in China. Moreover, better liquidity, higher cost efficiency, higher loan loss reserve and well-capitalization increase the non-performing loans. Additionally, the result of the interaction term (net loans to total assets × lending interest rate) indicates a negative influence on credit risk, which implies that although higher lending interest rate leads to higher credit risk, banks with more loanable assets are able to overcome the consequence of higher interest rate. The results are robust for both static and dynamic panel data estimation models. The results of this dissertation provide insights into the determinants of credit risk in China's economy.